Implementation of Lean Six Sigma to Reduce Work Time Waste in the Goods Transportation Department - Uni Pratama Pebrina Tarigan; Novemingsen, Rhevenson; Lu, David (Journal Knowledge Industrial Engineering (JKIE), 2023)
Lean Manufacturing is a manufacturing concept to seek to suppress waste or also known as waste. There are 7 wastes in Lean that need to be eliminated, which include: excessive production, inefficient material transportation, waiting time, value that has no added value, inventory, movement and defective products. Value stream mapping will be used in this study to identify waste and explore activities that have the potential to become wasteful. Opportunities for existing waste will be reduced so as not to result in waste. Research is expected to produce processes that are more efficient so as to reduce activities that do not have added value. That way it can overcome the company's problem that is often late in delivery.